DOUBLE MONITORING INDICES OF ARTERIAL PRESSURE AND THE LIPID PROFILE STATUS IN PATIENTS WITH DIABETES MELLITUS 1 AND 2 TYPE DEPENDING ON THE GLOMERULAR FILTRATION RATE - Pertseva, N.O.; Chub, D.I.; Gurzhiy, O.V. (World of Medicine and Biology, 2018)
The purpose of the study was to investigate the parameters of the blood pressure daily monitoring and features of the lipid profile in patients with type 1 and type 2 diabetes with different levels of eGFR. The study included 124 patients with diabetes. Of these, type 1 diabetes - 66 patients; type 2 diabetes - 58 patients. Patients were divided according to eGFR: 1st group - eGFR 90 ml / min / 1.73 m ² and above; 2nd group - eGFR from 89 to 60 ml / min / 1.73 m²; 3rd group - eGFR from 59 to 45 ml / min / 1.73 m². Each group was divided into su bgroups, depending on the type of diabetes. The results of the study showed that the disturbances in the daily BP values for the types "non-dipper" and "nighl-pcakcr" of patients with a decrease of eGFR were from 20% and 7.5% in the 1st group to 60.5% and 27.5% in 3rd group, respectively, indicating that these types are risk factors for the development of hypertension, as well as factors in the progression of diabetic kidney disease. Lipidogram indices changed significantly in the direction of hyperlipidemia with a decrease in eGFR, and strong and medium strengths of the correlation of total cholesterol, eGFR with 24- hour blood pressure monitoring indices allow to consider elevated lipidogram indices in patients with DM markers of the progression of diabetic nephropathy.
Keywords: lipidogram; blood pressure; type 1 and 2 diabetes mellitus; estimated glomerular filtration rate